Cultura e mudança organizacional: uma análise a partir da Lei de Acesso à Informação - GAMA, Merabe Carvalho Ferreira da (Universidade Federal do Pará, 2019)
This research aims to analyze the operationalization conditions for access to information at UFRA, due to Federal Law 12,527, of November 18th, 2011, at the headquarter campus of the Federal Rural University of Amazonia, in Belém. The publication of the law 12,527/2011 started a new way of public information treatment, by establishing rules for its access. In these terms, public agencies need to change and to adapt to the new scenario imposed by the law. The elements that will help on this process are based on the organizational culture, since many researchers have considered the Brazilian public service culture as a strong culture, resistant to changes and opposite to transparency. In this way, on the regulation process of the access to information is important to understand the factors involved on the transformation and to suggest mechanisms to facilitate its implementation. For this purpose, the methodology, classified as exploratory and descriptive, made use of field research as a technique of data collection in simple random probability sampling. The data treatment used descriptive and multivariate statistics. The results revealed aspects of organizational culture that characterize the process of organizational change. The research identifies four factors that affects access to information (Legitimacy in Public Administration, improper use of public information, social domain of the information and power and control of the public server), in addition to the presence of two groups (moderate and adaptive), one more open and other more afraid regarding access to information. Lastly, are proposed suggestions for the operationalization of Law 12,527/2011 at the university